Modelling the mechanical behaviour of metal powder during Die compaction process - G. Cricrì; M. Perrella (Fracture and Structural Integrity)
In this work, powder compaction process was investigated by using a numerical material model, which involves Mohr-Coulomb theory and an elliptical surface plasticity model. An effective algorithm was developed and implemented in the ANSYS finite element (FEM) code by using the subroutine USERMAT. Some simulations were performed to validate the proposed metal powder material model. The interaction between metal powder and die walls was considered by means of contact elements. In addition to the analysis of metal powder behaviour during compaction, the actions transmitted to die were also investigated, by considering different friction coefficients. This information is particularly useful for a correct die design.